(untitled) (Quaestiones Disputatae: temas en debate, 2020)
In this work we give an account of the political thought of two exponents of the second scholastic as they were to Francisco de Vitoria and Francisco Suarez. We will see how the uniqueness of the Republic is centered on conducting its own affairs independently of another political entity, in which it is integrated as a part. Political power does not reside in a mere aggregate of individuals, in which men go on to form a whole of order in solidarity in the attainment of a common political end; to that extent, the need for power appears. The ontological essence of authority, as a guiding principle, is not due to human consent, since it arises as a natural derivation of the social organism.